(untitled) (Annals of Medical Research, 2021)
Aim: Lumbosacral alignment has a potential role in providing proper spinal function, balanced and appropriate posture. The aim of our study was to compare lumbosacral angles between lumbar disc herniation and lumbar disc herniation-free patients. It was aimed to identify specific changes in lumbar disc herniation.Material and Methods: A total of 118 (69 female, 49 male) patients with the complaint of chronic low back pain were enrolled. Lumbar magnetic resonance images and standing lateral lumbar radiographs were obtained from the electronic hospital database. The presence or absence of disc herniation was diagnosed with lumbar magnetic resonance images. Measurement of lumbosacral angles were performed on the standing lateral lumbar radiographs.Results: Lumber lordosis angle and lumbosacral disc angle were significantly smaller in the lumbar disc herniation group (p = 0.033 and p = 0.038). No significant difference was detected in sacral tilt and lumbosacral angle (p = 0.705 and p = 0.413).Conclusion: The variations in lumbosacral angles cause changes in the spinal kinematics that may affect the occurrence of disc herniation. Loss of lumbar lordosis increases the compressive forces on the spine and may associate with the presence of disc herniation. Lumbosacral alignment must be taken into account when evaluate the pathophysiology of lumbar disc herniation.